2007
DOI: 10.1111/j.1365-2842.2007.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early biofilm formation on oral implants in man

Abstract: Biofilm formation on oral implants can cause inflammation of peri-implant tissues, which endangers the long-term success of osseointegrated implants. It has been reported previously that implants revealing signs of peri-implantitis contain subgingival microbiota similar to those of natural teeth with periodontitis. The purpose of the first part of this study was an atraumatic, quantitative investigation of biofilm formation on oral implant abutments; the objective of the second part was to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 24 publications
0
67
0
6
Order By: Relevance
“…6 Then, late colonizers, such as Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, are aggressive and damage periimplant tissue by a variety of putative virulence factors, such as lipopolysaccharide (LPS), proteolytic enzymes, and chondroitin sulfate, which activate the host immune response and cause the formation of a biofilm. 6,[8][9][10] The dental plaque on the abutment surface of supra gingiva can be cleaned by daily brushing but the subgingival plaque is not easily removed and creates a more suitable environment for the growth of periodontal pathogens. 10 Thus, the optimal surface of dental implant abutments should inhibit bacterial adhesion, especially in the early stages of biofilm formation.…”
Section: 2mentioning
confidence: 99%
“…6 Then, late colonizers, such as Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, are aggressive and damage periimplant tissue by a variety of putative virulence factors, such as lipopolysaccharide (LPS), proteolytic enzymes, and chondroitin sulfate, which activate the host immune response and cause the formation of a biofilm. 6,[8][9][10] The dental plaque on the abutment surface of supra gingiva can be cleaned by daily brushing but the subgingival plaque is not easily removed and creates a more suitable environment for the growth of periodontal pathogens. 10 Thus, the optimal surface of dental implant abutments should inhibit bacterial adhesion, especially in the early stages of biofilm formation.…”
Section: 2mentioning
confidence: 99%
“…Some of these studies reported similar supra and subgingival microbiota on teeth and Ti implants (Shibli et al, 2008, Furst et al, 2007, Groessner-Schreiber et al, 2004. In contrast, other studies found an absence of periodontal pathogens like Aggregatibacter (formerly Actinobacillus) actinomycetemcomitans and Porphyromonas gingivalis (Heuer et al, 2007) or sporadic high numbers of Parvimonas micra (formerly Peptostreptococcus micros), Staphylococcus aureus and Staphylococcus epidermidis (Furst et al, 2007, Salvi et al, 2008. The biofilm formation process is extremely complicated and this is particularly true when multiple species are present in the biofilm as in dental plaque.…”
Section: Introductionmentioning
confidence: 74%
“…Estos hallazgos concuerdan con la mayoría de las publicaciones consultadas, siendo el único autor que discrepa al respecto Heuer et al (2007). Estos autores, analizaron mediante PCR la presencia de Haemophilus actinomycetemcomitans, sinónimo de Aggregatibacter actinomycetemcomitans (Norskov-Lauritsen & Kiliany, 2006), y P. gingivalis, dos semanas después de la conexión, en 14 implantes colocados en 10 pacientes, obteniendo las muestras mediante conos de papel.…”
Section: Discussionunclassified